Feminization of the precarious at the UNAM: Examining obstacles to gender equality - Lu Ciccia; Geraldine Espinosa-Lugo; Graciela Garcia-Guzman; Jaime Gasca-Pineda; Patricia Velez; Laura Espinosa-Asuar (PLoS ONE, 2025)
The STEM workforce is marked by the persistent underrepresentation of women. Herein, we seek a better understanding of this gender gap in different science disciplines within Latin America. Specifically, we analyzed a case study: the professional development of women in science research institutes of the National Autonomous University of Mexico (UNAM). This interdisciplinary work analyzed quantitative and qualitative data through an intersectional philosophical lens, employing specific analytical tools drawn from feminist epistemology. We examined the interplay between horizontal and vertical segregation, symbolic and structural obstacles, and economic labor precariousness within the framework of gender norms. Shared trends in the Global North were analyzed to understand the perpetuation of gender stereotypes in the production of scientific knowledge. Additionally, we examined the relationship between the values embedded in gender norms and the cultural capital--here defined as encompassing both economic status and social legitimacy--associated with each discipline. Our findings indicate that, although women are underrepresented in pSTEM, they experience less vertical segregation than their counterparts in STEM related to the Natural Sciences. This suggests that knowledge areas currently associated with the highest cultural capital (pSTEM) may impose primarily symbolic rather than structural barriers for women. By contrast, in fields characterized by less masculine-coded values, women appear to face predominantly structural obstacles, as evidenced by the vertical segregation observed. These results contribute to a deeper understanding of the gender biases that exclude women from STEM disciplines.